Fabrication of Affordable and Sustainable Solar Cells Using NiO/TiO2 P-N Heterojunction - Kingsley O. Ukoba; Freddie L. Inambao; Andrew C. Eloka-Eboka (International Journal of Photoenergy)
The need for affordable, clean, efficient, and sustainable solar cells informed this study. Metal oxide TiO2/NiO heterojunction solar cells were fabricated using the spray pyrolysis technique. The optoelectronic properties of the heterojunction were determined. The fabricated solar cells exhibit a short-circuit current of 16.8 mA, open-circuit voltage of 350 mV, fill factor of 0.39, and conversion efficiency of 2.30% under 100 mW/cm2 illumination. This study will help advance the course for the development of low-cost, environmentally friendly, and sustainable solar cell materials from metal oxides.